Translation Strategies Of Idiomatic Expressions In Inside Out 2 Movie - Sari, Alexys Kartika; Mathilda, Bonaventura; Rosalinah, Yanti (Jurnal Multidisiplin Sahombu, 2025)
This study investigates the challenges and strategies employed in translating idiomatic expressions from English to Indonesian in the animated film Inside Out 2. It analyzes both official subtitles and fan-made subtitles to identify the types of idioms used and the translation strategies applied. A corpus of idiomatic expressions was collected and analyzed using a qualitative research approach. The findings reveal that various translation strategies, including literal translation, paraphrasing, and cultural substitution, were employed to translate idiomatic expressions into Indonesian. However, the effectiveness of these strategies varied, with some strategies resulting in more accurate and culturally appropriate translations than others. The study concludes that successful translation of idiomatic expressions requires a deep understanding of the source and target languages, cultural nuances, and the intended meaning of the original text.